ANALYSIS OF BUSINESS STRATEGY OF PT UNILEVER INDONESIA TBK USING SWOT MATRIX AND PESTEL: (CASE STUDY ON THE DECLINE IN COMPANY PROFITS IN 2024) - Wicaksono, Akbar Muhammad; Widjayanti, Arifiani (Airlangga Development Journal, 2025)
This study aims to analyze the business strategy of PT Unilever Indonesia Tbk in addressing a 29.8% profit decline in 2024, despite rising consumer spending. Using a qualitative descriptive method with a single-case approach, the research is based on secondary data such as financial and annual reports. SWOT and PESTEL analyses were employed to identify internal and external factors affecting performance. The findings reveal that cost pressures, shifting consumer behavior, boycott movements, and regulatory complexity contributed to the decline. However, digital supply chains, healthy lifestyle trends, and government stimulus present key opportunities. The study concludes that adaptive, efficient, and sustainable strategies are essential to maintaining competitiveness in the dynamic FMCG sector.